Development Transporation River On The Past Banjar Society - Rico, Muhammad; Nadilla, Dewicca Fatma; Al-Mujtaba, Parid Wajdi (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
The main problem examined in this research is the development of river transportation during the Banjarese era, the research results show that rivers are part of people's lives the city Banjarmasin, but currently the use of rivers as water transportation infrastructure appears be decreasing. Community activities in Banjarmasin City tend to shift to using land transportation. Apart from that, the lack of attention and participation by government, private sector and society in the field of river transportation has resulted river transportation being unable to compete with land transportation. As a city that has many rivers, almost all aspects of people's lives in Banjarmasin depend on rivers, both for daily activities and for economic activities. Not only that, there are even many community beliefs and traditions related to rivers. Therefore, it is not an exaggeration to say that river culture part of the life of the people of Banjarmasin. The existence of many rivers in the middle of city also encourages people to develop each area. And of is the : methode used this Is research uses historical methode throughted the Heuristic stage (data collection), internal and external criticism of the data obtained, interpretation and historiography of historical writing based on the data that has been obtained according to the researcher's objectives. The novelty of this research is that previous research did not specifically discuss the development of river transportation in the past in Banjarese society, most of which only revealed the history and phenomena, this made the researcher try to make this article specific